THE EFFECTS OF WORK DISCIPLINE, WORK MOTIVATION, AND WORK ENVIRONMENT ON TEACHER PERFORMANCE AT SMA PLUS ASSALAAM BANDUNG - Erlin Dianty; Ridlwan Muttaqin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to evaluate the impact of professional discipline, intrinsic motivation, and workplace conditions on educator productivity at SMA Plus Assalaam Bandung. The basis for this study arose from the discrepancy in teacher performance, which is still less than optimal, as evidenced by the lack of creativity in assignments and signs of disruption in discipline and enthusiasm. The research approach employed quantitative methods that were descriptive and verifiable. The research subjects included all 32 educational staff at SMA Plus Assalaam Bandung, using a total sampling technique. Information processing used multiple linear regression analysis, classical assumption checking, hypothesis testing, and the coefficient of determination. The research findings revealed that separately, professional discipline and intrinsic motivation have a positive and significant effect on educator productivity. However, workplace conditions did not show a significant influence. Together, these three factors contributed a 54.3% impact on educator productivity. The study concluded that to improve educator productivity, school leaders need to prioritize steadfastness in implementing discipline and developing intrinsic motivation.